2022
DOI: 10.1055/a-1945-8982
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CKM rs8111989 Polymorphism with Injury Epidemiology in Football Players

Abstract: The influence of the rs8111989 polymorphism in the muscle-specific creatine kinase gene (CKM) on injury incidence is unknown. The aim was to investigate CKM polymorphism on injury incidence in high-performance football players. A cohort of 109 high-performance players was genotyped by using saliva samples. Injury incidence was similar in players with the GG, GA, and AA genotypes and did not modify incidence duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(56 reference statements)
0
3
1
Order By: Relevance
“…There was an association between match and training injuries in muscle damage genes, such as the CKM c.*800A>G polymorphism, in which, when comparing training and match injuries, it was shown that the GG genotype and G allele lead to higher risks of training injuries in women's amateur football players. These data differ from those found in a recent study in which no association was found between this polymorphism and the risk of training and match injuries in men's professional football players [19]. To date, the CKM gene has not been extensively studied in relation to muscle injury, but it has been shown that it can be used for athlete selection due to the effect that the GG genotype has on muscle damage in football players [18,41].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…There was an association between match and training injuries in muscle damage genes, such as the CKM c.*800A>G polymorphism, in which, when comparing training and match injuries, it was shown that the GG genotype and G allele lead to higher risks of training injuries in women's amateur football players. These data differ from those found in a recent study in which no association was found between this polymorphism and the risk of training and match injuries in men's professional football players [19]. To date, the CKM gene has not been extensively studied in relation to muscle injury, but it has been shown that it can be used for athlete selection due to the effect that the GG genotype has on muscle damage in football players [18,41].…”
Section: Discussioncontrasting
confidence: 81%
“…In recent years, genetics, especially in single nucleotide polymorphism (SNP) studies, has provoked great interest in susceptibility to injury and in the characteristics of tissues that are more prone to injury, because these play such important roles [18][19][20]. Genetics play an important role in determining the structure and function of connective tissue such as muscles, tendons and ligaments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, combat athletes are more likely than untrained subjects to have the warrior ( COMT rs4680 GG) genotype [ 85 ], whilst chess players demonstrate an increased frequency of an allele linked to improved memory and spatial ability ( KIBRA rs17070145 T) [ 86 ]. Such discoveries demonstrate the broadening nature of sports genomics in recent times, with focus expanding from the traditional domain of investigating what makes elite performers different from the general population into other domains, such as sports nutrigenetics [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] and areas of sports medicine, such as genomic variants associated with soft-tissue injuries and sports-related concussion [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Introductionmentioning
confidence: 99%